Alkynyl‐Functionalized Imidazolium for "Click" Dendrimer Functionalisation and Palladium Nanoparticle Stabilization. Issue 8 (9th February 2015) - Deraedt, Christophe; d'Halluin, Martin; Lesturgez, Stephanie; Salmon, Lionel; Goglio, Graziella; Ruiz, Jaime; Astruc, Didier
Abstract: Functionalization of imidazolium salts (IMSs) that allow easy derivation of molecular or solid supports are called for in various applications. Here, the synthesis of an alkyne‐containing IMS can be achieved in three steps from 2, 4, 6‐trimethylaniline, and this IMS can be further successfully functionalized by using either Sonogashira or a "click" CuAAC reaction that was applied to dendritic IMS synthesis giving high yields. Applications are illustrated for Pd nanoparticle stabilization by the IMS dendrimer for Suzuki–Miyaura catalysis. Abstract : An imidazolium salt containing an alkynyl group was synthesized in three steps in order to functionalize nanomaterials by means of CuAAC and Sonogashira reactions. For instance, a nona‐azido dendritic core could be "clicked" with the alkynyl‐containing imidazolium salt. The resulting dendrimer allows the stabilization of palladium nanoparticles that are active in the Suzuki–Miyaura cross‐coupling reaction.